Efficacy and safety of endovascular treatment in patients older than 90 with acute ischemic stroke: A retrospective cohort study - Friedman, Itamar; Naftali, Jonathan; Pardo, Keshet; Findler, Michael; Barnea, Rani; Brauner, Ran; Perlow, Alin; Auriel, Eitan; Raphaeli, Guy (Frontiers in Neurology, 2022)
Background Endovascular treatment (EVT) for acute ischemic stroke (AIS) with large vessel occlusion (LVO) is the standard of care treatment today. Although elderly patients comprise the majority of stroke patients, octogenarians and non-agenarians are often poorly represented or even excluded in clinical trials. We looked at the safety and efficacy of EVT for AIS with LVO in patients over 90 (Non-agenarians), in comparison to patients aged 80–89 (Octogenarians) and to patients younger than 80 years (<80yrs). Methods A retrospective analysis of patients who underwent EVT in a single stroke center during 2015–2019. Patients were divided into three subgroups based on their age: Non-agenarians, Octogenarians, and patients <80 yrs. The groups were compared based on baseline characteristics and stroke variables. In addition, we compared clinical and radiological outcomes including functional outcomes measured by the modified ranking scale (mRS) at day 90, symptomatic intracranial hemorrhage (sICH), and mortality. Results Three hundred and forty seven patients were included, 20 (5.7%) of them were non-agenarians, 96 (27.7%) were octogenarians and 231 (66.6%) were <80 yrs. No statistically significant differences were found between groups regarding baseline characteristics, cardiovascular risk factors, stroke variables, or successful revascularization rates. Puncture to recanalization time intervals showed an age-related non-significant increase between the groups with a median time of 67.8, 51.6, and 40.2 min of the non-agenarian, octogenarian, and <80 yrs groups, respectively (p-value = 0.3). Favorable outcome (mRS 0–2) was 15% in non-agenarians vs. 13.54% in octogenarians (p-value = 1) and 40.2% in <80 yrs. sICH occurred among 5% of non-agenarians, compared to 4% among octogenarians (p-value = 1) and 2.6% in <80 yrs. The mortality rate at 3 months was significantly higher (55%) in non-agenarians compared to octogenarians (28%) (p-value = 0.03) and to <80 yrs (19.48%). Conclusion EVT in nonagenarians demonstrated a high rate of successful revascularization, whilst also showing an increased rate of sICH when compared to octogenarians. Mortality rates showed an age-related correlation. Although further studies are needed to clarify the patient selection algorithm and identify sub-groups of elderly patients that could benefit from EVT, we showed that some patients do benefit from EVT therefore exclusion should not be based on age alone.